Application of time–frequency analysis to the evaluation of the condition of car suspension. (June 2015) - Szymański, G.M.; Josko, M.; Tomaszewski, F.; Filipiak, R.
Abstract: The article presents possibilities of use of vibration signal parameters for the evaluation of elements׳ clearance in the car suspension system. The time-spectrum analysis has been proposed to determine the frequency band connected with car body free vibration generated by impacts of suspension elements in case of clearance in suspension elements fixing to the car body. Diagnostic models allowing evaluation of shock absorber fastening to the car body are described in this work. Highlights: We diagnose car suspension. We diagnose vibration signal. We filter vibration signal in resonance band. We determine resonance band on the basis of time–frequency analysis. Filtration of vibration signal increases the dynamics of diagnostic parameter.